Cyclic nucleotide in oocyte In vitro maturation in Assisted Reproductive Technology - Christie L Sun; Sally L Catt; Kiri Beilby; Mulyoto Pangestu (Faculty of Medicine, Diponegoro University, 2020)
In vitro maturation (IVM) is a promising assisted reproductive technology (ART) for human infertility treatment. However, when cumulus oocyte complexes (COCs) are removed from their follicular environment when manipulated in vitro, it can lead to a decrease of intra-oocyte cyclic adenosine 3’, 5’-monophosphare (cAMP) causing spontaneous nuclear maturation and an asynchrony with the oocytes’ cytoplasmic maturation, resulting in poor embryo developmental outcomes. Nuclear and cytoplasmic synchrony is important during oocyte maturation within antral follicles.It is maintained partially by the actions of c-type natriuretic peptide (CNP) binding with natriuretic peptide receptor 2 (NPR2), supporting high cAMP levels thus holding the oocyte in meiotic arrest. Addition of CNP to pre-IVM media has the capacity of maintaining cAMP levels and thus improve synchrony. Moreover, in women with advanced maternal age, successful IVM of aging oocytes faces significant challenges due to the morphological and cellular changes. Inhibiting initiation of nuclear maturation by cAMP modulator, CNP during pre-IVM period and thus improve oocyte developmental competence regardless of oocyte age.